2015
DOI: 10.1088/0004-637x/813/1/36
|View full text |Cite
|
Sign up to set email alerts
|

ON THE [C ii]–SFR RELATION IN HIGH REDSHIFT GALAXIES

Abstract: After two ALMA observing cycles, only a handful of [C II] 158 µm emission line searches in z > 6 galaxies have reported a positive detection, questioning the applicability of the local [C II]-SFR relation to high-z systems. To investigate this issue we use the Vallini et al. (2013, V13) model, based on high-resolution, radiative transfer cosmological simulations to predict the [C II] emission from the interstellar medium of a z ≈ 7 (halo mass M h = 1.17 × 10 11 M ) galaxy. We improve the V13 model by includin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
348
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 214 publications
(391 citation statements)
references
References 93 publications
(124 reference statements)
37
348
3
Order By: Relevance
“…We conclude that about 70% (±20%) of the flux in the [Cii] system is extended and diffuse on scales larger than about 1 kpc, which is consistent with the idea that the bulk of the [Cii] emission is associated with relatively diffuse gas on scale larger than the star formign regions, as expected by recent model of primeval galaxies (e.g. Vallini et al 2013Vallini et al , 2015Pallottini et al 2017;Katz et al 2016).…”
Section: [Cii] Emissionsupporting
confidence: 91%
See 2 more Smart Citations
“…We conclude that about 70% (±20%) of the flux in the [Cii] system is extended and diffuse on scales larger than about 1 kpc, which is consistent with the idea that the bulk of the [Cii] emission is associated with relatively diffuse gas on scale larger than the star formign regions, as expected by recent model of primeval galaxies (e.g. Vallini et al 2013Vallini et al , 2015Pallottini et al 2017;Katz et al 2016).…”
Section: [Cii] Emissionsupporting
confidence: 91%
“…Vallini et al (2017) suggests that an offset between [Cii] emission and UV-stellar emission could result from a strong feedback effect, which could clean the most vigorous star forming regions, or even the entire galaxy, from the bulk of the molecular gas. Low metallicity and chemical inhomogeneity are also invoked as possible causes of the faintness of the [Cii] emission; indeed, metallicity effects were already proposed in Vallini et al (2015) to be one of the major cause of the deficit of the [Cii]-SFR relation observed at high-redshift relative to the local one (e.g. De Looze et al 2014).…”
Section: Theoretical Scenarios and Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various sub-grid "gas physics" approaches have been applied to both semi-analytical (Muñoz & Furlanetto 2014;Popping et al 2014a) and hydrodynamical (Nagamine et al 2006;Vallini et al 2013Vallini et al , 2015 simulations of galaxies. The simulations by Nagamine et al (2006) focus on the C II [ ] detectability of lyman break galaxies (LBGs) at z=3, while Vallini et al (2013) apply their simulations to observed upper limits on the C II [ ] emission from the z=6.6 Lyα emitter (LAE) Himiko (Ouchi et al 2013) finding that its metallicity must be subsolar.…”
Section: IImentioning
confidence: 99%
“…Both set of simulations consider a two-phase ISM consisting of a cold and a warm neutral in pressure equilibrium, and both find that the C II [ ] emission is dominated by the cold neutral medium (CNM). In an update of their 2013 simulation, that includes the C II [ ] contribution from PDRs and a non-uniform metallicity distribution in the gas phase, Vallini et al (2015) finds that most of the C II [ ] emission from their z=6.6 models originates in the PDRs with only~10% coming from the CNM.…”
Section: IImentioning
confidence: 99%